Role of Acinetobacter baumannii in decolorization of reactive blue 224 dye and functional analysis of azoreductase gene - Ullah F.; Mustafa G.; Tariq Zahid M.; Jamil I.; Zaghum Abbas S.; Jeon B.-H.; Alessa A.H.; Rafatullah M. (Elsevier B.V., 2025)
Bioremediation is a sustainable and worthy approach for remediating textile industrial wastewater, which poses severe extortions to human and environmental health due to its toxic, mutagenic, and carcinogenic nature. The present study employed Acinetobacter baumannii 1005 isolated from industrial wastewater to emphasize its degradation potential and to characterize the azoreductase (AZA) gene to assess and optimize the biodegradation of reactive blue 224 (RB-224) textile dye. A. baumannii showed significant decolorization against RB-224, resulting in a change in color. Under optimized conditions (pH 6, 37 C, and 100 mg/L), A. baumannii exhibited 91 % decolorization of RB-224 being analyzed by UV?vis after 24 h of incubation. UV?vis spectroscopy and FTIR analysis have shown the efficiency of A. baumannii for degrading RB-224. In the UV spectrum, the shifting of the peak from560 nm to 400 nm confirmed the decolorization. In the FTIR spectrum, the shift of several significant peaks related to the functional groups S = O C-N, C?H, C = C, and N?H, corresponding to the structure of RB-224 dye along with the emergence of new peaks indicating the formation of metabolites after degradation. The Azoreductase (AZA) gene of ?600 bp was amplified and cloned in a pTz57R/T cloning vector. Subsequently, the AZA gene was sequenced and submitted to NCBI for accession number. This study explored the potential of A. baumannii isolate suitable for the bio-remediation of textile dyes. ? 2024 The Author(s)